KEMATANGAN KARIER MAHASISWA TINGKAT AKHIR PROGRAM STUDI BIMBINGAN DAN KONSELING UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA - Erwita Ika Violina (Jurnal Penelitian Bimbingan dan Konseling, 2017)
Career maturity is readiness of individuals to deal with the tasks of the development of his/her career.Student’s career maturity can be seen through the readiness of students to work in accordance with their education. This study aims to describe the career maturity oflast term Guidance and Counseling University of Muhammadiyah University of North Sumatra students. The population in this study is 146last term of the guidance and counseling Muhammadiyah University Sumatera Utara students, with the samples are 105 students selected by simple random sampling technique. The instrument used in this study is the scale of career maturity. The results show that 1.9% of students have very low career maturity, 5.7% are in low career maturity, 40% are in mature career, 50.5% are in high career maturity, and 1.9% are in very high career maturity.Keywords: career maturity, last term guidance and counseling students